PENGARUH PENGGUNAAN MEDIA SPATIAL EXPLORATION DALAM MENINGKATKAN KEMAMPUAN BERPIKIR SPASIAL SISWA PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 8 PEKANBARU - Viola Salsa Billa Anshari; Suasti, Yurni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of using spatial exploration media on improving students' spatial thinking skills at SMA Negeri 8 Pekanbaru. The method used in this study is a quasi-experimental method with a pretest-posttest control group research design. The research sample consisted of class XI.4 as the experimental class and class XI.1 as the control class, selected randomly. Spatial thinking data were collected through tests and analyzed using a T-test. The results of the study found that there is an effect of spatial exploration media on the spatial thinking of 11th-grade students at SMA Negeri 8 Pekanbaru, with the average posttest score of the experimental class being 84, higher than the control class, which was 71.